Gastric Involvement in Autoimmune Pancreatitis: MDCT and Histopathologic Features - Baez, Juan C; Hamilton, Matthew J; Bellizzi, Andrew; Mortelé, Koenraad J (JOP. Journal of the Pancreas, 2010)
Context Autoimmune pancreatitis is a relatively rare, yet well described cause of chronic pancreatitis. Extrapancreatic findings are now recognized as important manifestations of this entity and viewed as part of a larger disease process tentatively named “IgG4-associated sclerotic disease”. Case report We herein report a case of autoimmune pancreatitis with histopathologically proven gastric involvement. We also describe and illustrate the multidetector-row computed tomography appearance of gastric involvement in IgG4-associated sclerotic disease. Conclusion Autoimmune pancreatitis is increasingly recognized as a multi-systemic disease whose early recognition dramatically affects patient management. Knowledge of the computed tomography appearance of gastric involvement in autoimmune pancreatitis can aid in diagnosis. Image: Endoscopic image demonstrates non-erosive gastric inflammation.